"It's easy to throw rocks at a corporation": wind energy development and distributive justice in Canada. Issue 6 (2nd November 2017) - Walker, Chad; Baxter, Jamie
ABSTRACT: In places like Canada, fast-paced wind turbine development combined with policy that limits local decision-making power has resulted in strong opposition to specific projects. Some studies suggest that anti-wind sentiment is tied to inadequate financial benefits – especially sharing at the local level. Thus, ideas of distributive economic justice have received traction, particularly in the form of praise for community-based development models. This paper reports on the findings from a mixed-methods study concerning preferred distributive justice elements in rural communities in Ontario (technocratic-based model) and Nova Scotia (community-based model) living with turbines. Residents' perceptions of economic benefits are nuanced, but unlike other studies, this empirical work shows that both the fair distribution and the amount of local benefits are important predictors of project support. Yet, concerns around the fair distribution of benefits dominate in a regression on the adequacy of those benefits. A variety of interview and survey findings further point to the strength of traditional, profit-sharing community-based models for distributing benefits, but also more novel ideas including lowered electricity bills and tax rebates in areas home to turbines.